EPIDEMIOLOGY OF ROAD TRAFFIC CRASHES AMONG LONG DISTANCE DRIVERS IN IBADAN METROPOLIS, OYO STATE (2014)
Road Traffic Crashes (RTC) are major causes of morbidity and mortality in Nigeria. While previous studies had reported increases in RTC among long distance drivers and had associated this with their risky behaviours, not many have focused on the distribution and determinants of RTC among long distance drivers in Ibadan metropolis. Information about the distribution of the risk factors of RTC among this group of drivers could be used to design, implement and evaluate interventions to reduce the risk. Hence, this study was conducted to describe the distribution of RTC by place, time of occurrence, characteristics of persons involved and identify factors associated with RTC among long distance drivers in Ibadan metropolis. Using a cross-sectional study, a two-stage sampling technique was used to select 594 consenting long distance drivers from 5 out of 12 major motor parks in Ibadan metropolis. A pretested interviewer-administered semi-structured questionnaire was used to collect data on socio-demographic characteristics, driving history, knowledge of road safety measures, perceived effects of use of psychoactive drugs on the safety behaviours and mobile phone when driving. Also incorporated in the questionnaire were history of RTC including place and time of occurrence of the last crash. Knowledge of road safety measures was scored based on drivers’ understanding of 7 road safety measures comprising speed and the six road safety signs, with scores ≥4 indicating good knowledge. Data were analysed using descriptive statistics, Chi-square test and logistic regression with level of significance set at 0.05. Respondents were males, with median age of 42.0 years (range: 20.0-73.0 years). Secondary education was the highest level of education attained by 38.0%. Most (96.3%) had been driving for more than five years and 77.7% had poor knowledge of road safety measures. About 23.6% reported the use of mobile phone when driving while, 38.7% and 33.8% reported current use of kolanut and alcohol respectively. The life time prevalence of RTC was 35.5% while 16.2% reported having had at least one RTC in the year preceding the study. The RTCs occurred mainly on narrow roads (25.0%) and bad portions of tarred roads (32.0%) with peak occurrence on weekends (Fridays- 20.0% and Saturdays- 21.3%) and in the afternoon (33.1%). Significantly higher proportions of drivers aged ≤39 years (23.9%), those with no formal education (29.9%), those who reported the use of mobile phone when driving (27.9%), those who reported alcohol (21.9%) and Kola nut use (19.6%) were involved in RTC in the last one year. A significant predictor of the last episode of RTC in the last one year was alcohol use (OR=1.8, CI=1.1-2.9). Road Traffic Crashes occurred mostly among long distance drivers who were young, non-formally educated, alcohol users and mobile phone users when driving. Discouraging the use of alcohol, kolanut and mobile phones when driving, as well as the implementation of road safety education programme among young and uneducated drivers is recommended.